Feed consumption and utilisation in female western tarsier (Tarsius bancanus) in captivity - WARTIKA ROSA FARIDA; KHIKMAH KUSUMA WARDANI; ANITA SARDIANA TJAKRADIDJAJA; DIDID DIAPARI (Society for Indonesian Biodiversity, 2008)
Western tarsier (Tarsius bancanus), one of protected Indonesian wildlife is endemic primate of Bangka, Sumatra, Kalimantan and Natuna Islands. Studies on nutrition requirement through feed consumption and utilization of western tarsier was conducted in the Small Mammal Captivity of Zoology Division, Research Center for Biology, Indonesian Institute of Sciences (LIPI) Cibinong, Bogor. The results indicated that average of dry matter intake was 4.05±0.14 g/head/day or 4.01±0.24% of body weight. Diets given were cricket and grasshopper, considered high coefficient of dry matter digestibility (94.33±1.76%). Average of the following nutrient intake was ash 4.12±0.04%; crude protein 64.52±0.49%; fat 12.82±0.68%; crude fiber 6.59±0.11%; nitrogen free extract 12.03±0.79% and gross energy 23.54±0.67 kcal/head/day. Average of body weight gain of western tarsier at this experiment was 0.5 5± 0.2 g/head/day with average of feed efficiency was 13.39±4.66% and protein efficiency ratio was 0.21±0.07 g/day. Average of total digestible nutrient (TDN) was 67.42±0.97%.© 2008 Jurusan Biologi FMIPA UNS SurakartaKey words: consumption, feed utilisation, Tarsius bancanus, captivity.